Ergonomic Risk Assessments (ERA) on Cycling Posture using Rapid Upper Limb Assessment (RULA) and Rapid Entire Body Assessment (REBA) Method among Cyclists - ABDUL HADI, MOHAMAD HAFIZUL IKRAM BIN ABDUL HADI; MOHD NASRULL BIN ABDOL RAHMAN (Research Progress in Mechanical and Manufacturing Engineering, 2022)
This research utilised an Ergonomic Risk Assessments (ERA) analysis of cyclists’ body posture in order to determine the limb hazards associated with cyclists who are at risk for musculoskeletal illnesses (MSD). This is because riding a bike requires unusual body postures such as bending, sitting, and standing. To lower the risk of MSD, researchers conducted ergonomic assessments directly in the activity area using the RULA and REBA methodologies. This study was done in the state of Kelantan, and the survey respondents included multiple male bikers (N=95). This study examined three distinct types of bicycles: road bikes, mountain bikes, and folding bikes. The age range of respondents for road bikes (N=31) ranged from 22 to 36 years (29.55±3.45). Meanwhile, mountain bikes (N=33) were between 23 to 35 years old (28.94±3.05), and folding bikes (N=31) were between 25 to 32 years old (28.81±1.85). The results showed that for road cyclists, the body postures assessed by RULA were at Action Levels 2 (54.84%) and 3 (45.16%), while REBA all passed Action Levels 3 (100%). For mountain cyclists results, the average was at Action Levels 2 (RULA:75.76%, REBA:15.15%) and 3 (RULA:24.24%, REBA:84.85%). Results for folding cyclists the body posture assessed by RULA at Action Levels 1 (61.29%), 2 (29.03%), and 3 (9.68%). Meanwhile, REBA was evaluated at Action Levels 2 (45.16%) and 3 (54.84%). In conclusion, combination of risks leads to high increase of ERAs among cyclists.